Molecular characterization and functional analysis of peroxiredoxin 4 in grass carp (Ctenopharyngodon idella). (December 2021) - Liang, Xinyu; Zhu, Denghui; Li, Yongming; Liao, Lanjie; Yang, Cheng; Liu, Liyue; Huang, Rong; Wang, Weiyan; Zhu, Zuoyan; He, Libo; Wang, Yaping
Abstract: Peroxiredoxins (Prxs) are a group of evolutionarily conserved selenium-independent thiol-specific antioxidant proteins. In this study, the peroxiredoxin-4 ( CiPrx4 ) gene from grass carp was identified and characterized. The full-length of CiPrx4 is 1339 bp, encoding 260 amino acids that contain two peroxiredoxin signature motifs and two GVL motifs. CiPrx4 belongs to the typical 2-Cys subfamily and shows the highest homology with Prx4 from Cyprinus carpio (95.4%). CiPrx4 mRNA was constitutively expressed in all tested tissues and was upregulated by grass carp reovirus and pathogen-associated molecular pattern (PAMP) stimulation. CiPrx4 was localized in the cytoplasm and co-localized with the endoplasmic reticulum. The purified CiPrx4 protein protected DNA from degradation in a dose-dependent manner. Moreover, the overexpression of CiPrx4 in Escherichia coli and fish cells showed apparent antioxidant and antiviral activities. Collectively, the results of the present study provide new insights for further understanding the functions of Prx4 in teleost fish. Highlights: Peroxiredoxin 4 gene from grass carp ( CiPrx4 ) was cloned and characterized. CiPrx4 localized in cytoplasm and co-localized with the endoplasmic reticulum. CiPrx4 could prevent DNA from degradation caused by reactive oxygen species. CiPrx4 showed apparent antioxidant activity and anti-viral effects.